Biosimilar development and review process in the BRICS-TM countries: Proposal for a standardized model to improve regulatory performance. Issue 2 (1st February 2022) - Rahalkar, Hasumati; Sheppard, Alan; Salek, Sam
ABSTRACT: Objectives: The current study is aimed at proposing a standardized regulatory model for biosimilar development and approval for adoption by BRICS-TM agencies, based on evaluation of regulatory guidelines and potential solutions to challenges. Methods: An established validated questionnaire was used and the recommendations were collated. Propositions deemed critical for improving the regulatory pathway for biosimilar development were synthesized to design a new regulatory model. Results: The key areas for improvement in BRICS-TM countries were: effective implementation of a step-wise approach; adoption of science-based regulatory evaluation for clinical efficacy studies and acceptance of analytical comparability studies in lieu of confirmatory clinical trials; a streamlined biosimilar development program for RBP sourcing; regulatory reliance for joint or shared review of the applications; and enhanced transparency and communication between the regulatory agencies and biosimilar developers. Based on these identified critical aspects, a simplified and standard regulatory model was developed to enable standardization of biosimilar guidelines across BRICS-TM countries for a common development program. Conclusions: Effective implementation of the proposed standardized model for biosimilar development and approval processes across the BRICS-TM agencies will eliminate unwarranted studies, reduce the development costs, and enhance process efficiency thereby expediting patients' access to new affordable biosimilar medicines. Plain language summary The studies presented in this article have identified key areas for improvement in biosimilar development and approval pathways in BRICS-TM countries, which have formed the basis for development of a model to standardize requirements for biosimilar development and the approval process, with a view to improve regulatory performance. Implementation of the proposed model by the BRICS-TM regulatory agencies with consideration of a stepwise approach and science-based evaluation of analytical data could reduce the duplication and unnecessary conduct of non-clinical studies, thereby reducing the development cost and review timelines. Data assessment based on reliance as considered in the proposed model would strengthen reliance networks and improve the process efficiency among the BRICS-TM regulatory agencies. Flexibility in regulatory requirements by the BRICS-TM agencies for the use of Reference Biologic Product (RBP) from other emerging economies and their interaction with the developers would enhance transparency and ease the challenges in sourcing RBP from different jurisdictions. This would further help in expediting a common biosimilar development process. Good Manufacturing Practice (GMP) inspection of the biosimilar manufacturing facilities by desktop audit or off-site audit and acceptance of GMP certifications from other reference agencies would improve the overall regulatory performance and reduce overall review timelines, leading to faster availability of biosimilar medicines for patient access.